Effects of CO2 adsorption on proton migration on a hydrated ZrO2 surface: an ab initio molecular dynamics study. Issue 30 (20th July 2017) - Sato, Ryuhei; Shibuta, Yasushi; Shimojo, Fuyuki; Yamaguchi, Shu
Abstract : Carbonate formation reduces the basicity of surface oxide ions selectively and subsequently reduces the proton hole defects (Zr–OH − ). Abstract : Hydration reactions on a carbonate-terminated cubic ZrO2 (110) surface were analyzed using ab initio molecular dynamics (AIMD) simulations. After hydration reactions, carbonates were still present on the surface at 500 K. However, these carbonates are very weak conjugate bases and only act as steric hindrance in proton hopping processes between acidic chemisorbed H2 O molecules (Zr–OH2 ) and monodentate hydroxyl groups (Zr–OH − ). Similar to a carbonate-free hydrated surface, Zr–OH2, Zr–OH −, and polydentate hydroxyl groups (OH + ) were observed, while the ratio of acidic Zr–OH2 was significantly larger than that on the carbonate-free hydrated surface. A thermodynamic discussion and bond property analysis reveal that CO2 adsorption significantly decreases the basicity of surface oxide ions (O), whereas the acidity of Zr–OH2 is not affected. As a result, protons released from OH + react with Zr–OH − to form Zr–OH2, leading to a deficiency of proton acceptor sites, which decreases the proton conductivity by the hopping mechanism.